Endobronchial Cartilage Rupture: A Rare Cause of Lobar Collapse - Osama Dasa; Nauman Siddiqui; Mohammed Ruzieh; Toseef Javaid (Case Reports in Pulmonology)
Endobronchial cartilage rupture is a rare clinical condition, which can present in patients with severe emphysema with sudden onset shortness of breath. We present a case of a 62-year-old male who presented to our emergency department with sudden onset shortness of breath. Chest X-ray showed lung hyperinflation and a right lung field vague small density. Chest Computed Tomography confirmed the presence of right middle lobe collapse. Bronchoscopy revealed partial right middle lobe atelectasis and an endobronchial cartilage rupture. Endobronchial cartilage rupture is a rare condition that can present as sudden onset shortness of breath due to lobar collapse in patients with emphysema and can be triggered by cough. Bronchoscopic findings include finding a collapsed lung lobe and a visible ruptured endobronchial cartilage. A high index of suspicion, chest imaging, and early bronchoscopy can aid in the diagnosis and help prevent complications.